25.5k views
1 vote
X - 3(x – 7) = 4(x – 7) – 2x​

2 Answers

2 votes

Answer: x=12.25

Step-by-step explanation: First, multiply the numbers into the parentheses. You will get:

X -3x +21 = 4x -28 -2x

Combine like terms.

-2x +21 =2x -28

Isolate x by adding 2x to each side.

21 =4x -28

Add 28 to each side to get x by itself.

49=4x

Divide by 4.

X =12.25

User Jonas Anso
by
5.1k points
5 votes

Answer:

x = 12.25

Explanation:

Given

x - 3(x - 7) = 4(x - 7) - 2x ← distribute parenthesis on both sides

x - 3x + 21 = 4x - 28 - 2x ← simplify both sides

- 2x + 21 = 2x - 28 ( subtract 2x from both sides )

- 4x + 21 = - 28 ( subtract 21 from both sides )

- 4x = - 49 ( divide both sides by - 4 )

x =
(49)/(4) = 12.25

User Loyal
by
5.4k points